Patient-Reported Financial Burden Following Stereotactic Body Radiation Therapy for Localized Prostate Cancer - Sholklapper, Tamir N.; Creswell, Michael L.; Payne, Alexandra T.; Markel, Michael; Pepin, Abigail; Carrasquilla, Michael; Zwart, Alan; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Collins, Brian; Kumar, Deepak; et al. (Frontiers in Oncology, 2022)
Introduction and Objectives: In patients with localized prostate cancer, 5-fraction, Stereotactic Body Radiation Therapy (SBRT) has been found to offer comparable oncologic outcomes and potential for improved treatment compliance compared to conventional, 40-plus fraction radiation therapy (RT). Recent studies of oncologic patient experiences have highlighted both the impact of therapy-associated financial toxicity (FT) on treatment adherence and health-related quality of life (HRQOL). Methods: Cross-sectional assessment of FT after SBRT using the 12-item COST questionnaire. Total questionnaire score (range 0-44) to evaluate FT grade (0-3), with higher COST value representing lower grade. Patient zip code used to approximate distance from index hospital. Univariate and multivariate analyses of average COST score (0-4). Results: Response rate of 57.5% (332 of 575 consented patients) with 90.7%, 8.2%, and 1.1% experiencing grade 0, 1, and 2 FT, respectively, with no grade 3. Unemployment or disability, non-white race, low income, and concurrent hormonal therapy associated with a statistically significant worse FT (lower COST value) on univariate and multivariate analysis (p<0.05). Education level and insurance status significant on univariate analysis only. Non-statistically significant difference in age, marital status, time since treatment, and distance from index hospital. Conclusions: SBRT associated with low FT. However, statistically significant socioeconomic disparities in FT remain despite ultra-hypofractionated treatment.